Menstrual Effluent Provides a Novel Diagnostic Window on the Pathogenesis of Endometriosis - Nayyar, Ashima; Saleem, Matthew I.; Yilmaz, Mine; DeFranco, Margaret; Klein, Gila; Elmaliki, Kristine Mae; Kowalsky, Elena; Chatterjee, Prodyot K.; Xue, Xiangying; Viswanathan, Radhika; Shih, Andrew J.; Gregersen, Peter K.; et al. (Frontiers in Reproductive Health, 2020)
Endometriosis is a chronic inflammatory disorder characterized by the presence of endometrial-like tissue growing outside of the uterus. Although the cause is unknown, retrograde menstruation leads to deposition of endometrial cells into the peritoneal cavity. Lack of disease recognition and long diagnostic delays (6-10 years) lead to substantial personal, social and financial burdens, as well as delayed treatment. A non-invasive diagnostic for endometriosis is a major unmet clinical need. Here, we assessed whether differences in menstrual effluent-derived stromal fibroblast cells (ME-SFCs) from women with and without endometriosis provide the basis for a non-invasive diagnostic for endometriosis. In addition, we investigated whether treatment of control ME-SFCs with inflammatory cytokines (TNF and IL-1β) could induce an endometriosis-like phenotype. ME-SFCs from laparoscopically diagnosed endometriosis patients exhibit reduced decidualization capacity, measured by IGFBP1 production after exposure to cAMP. A receiver operating characteristic (ROC) curve developed using decidualization data from controls and endometriosis subjects yielded an area under the curve of 0.92. In addition, a significant reduction in ALDH1A1 gene expression and increased podoplanin surface expression were also observed in endometriosis ME-SFCs when compared to control ME-SFCs. These endometriosis-like phenotypes can be reproduced in control ME-SFCs by exposure to inflammatory cytokines (TNF and IL-1β) and are associated with increased cell migration. These results are consistent with the hypothesis that chronic intrauterine inflammation influences the development of endometriosis lesions following retrograde menstruation. In conclusion, the analysis of ME-SFCs can provide an accurate, rapid and non-invasive diagnostic for endometriosis and insight into disease pathogenesis.